IDENTITAS DAN KESARJANAAN: MELINTASI BATAS DALAM STUDI TENTANG AHMADIYAH DI INDONESIA - Ahmad Najib Burhani (Harmoni, 2017)
Who is more authoritative in researching certain religious minorities, insider or outsider? How to apply the concept of ‘detachment’, ‘neutrality’, and ‘bracketing’ in studying religious groups officially declared by majority of ulama and mainstream religious organizations as deviant cults like Ahmadiyah? And how would the various concepts, methods, and scientific theories, such as ‘going native’ and ‘participant observation’ be applied in the field? How to negotiate between faith and science, our identity as part of religious mainstream and orthodox group in studying communities deemed ‘heretic’? How does researcher’s identity as a non-Ahmadi affect his research and judgment about Ahmadiyah? This paper intends to discuss the author’s experience in studying Ahmadiyah, in applying various theories and academic principles in the study of this community, and how to behave towards individual conflicts and controversies surrounding Ahmadiyah issues. This paper is based on seven-year experience of living with, studying, and participating in the activities of Ahmadiyah in Indonesia, Singapore, Japan, India, England, and the United States.